Generalized notions of continued fractions : ergodicity and number theoretic applications /: ergodicity and number theoretic applications. (2023) - (Mathematician), Fernández Sánchez, Juan; López-Salazar Codes, Jerónimo; Seoane Sepúlveda, Juan B; Trutschnig, Wolfgang
No abstract available